Performative Prayers of a Prophet: Investigating the Prayers of Jonah as Speech Acts - Mann, Steven, T. (2017)
Discussions of the Book of Jonah often pay little attention to Jonah’s prayers (Jonah 2:1–9 [2–10]; 4:2–3). Consideration of these prayers as speech acts offers several insights into the ways in which these texts are integral to the book as a whole. In this study, I investigate these prayers for their function within the world of the narrative (the story level) as well as within the world of the audience (the storyteller level). On the story level, Jonah uses these prayers to celebrate as well as to appeal to Yhwh’s commitment ([inline-graphic 01i]) in his own situation. He also explains his theological motivation for disobeying Yhwh’s directive at the beginning of the story. On the storyteller level, these prayers attempt to foster a hermeneutic of self-involvement in the audience that will enable them to view this book not merely as a story about Jonah but as a story about themselves.
Keywords: Chiasm; [inline-graphic 02]; psalms of thanksgiving; Hermeneutics; Speech Act Theory; Prayer; Jonah